Arte e natura: il ripensamento del tema della imitatio in Nicola Cusano - André, João Maria (2019)
In this article, after a contextualization of the theme ‘art and nature’ in current times and in the Renaissance period, in Nicholas of Cusa’s thought and in its mystical and Neoplatonic sources, we try to situate the question of art in the circle of the “Dionysian erotic” and in its symbolic and doxological meaning. In a second moment, we consider the concept of imitatio in ancient and medieval thought, as a conceptual mediation for thinking the relation between art and nature. In a third moment, we analyze the different occurrences of the “ars imitatur naturam” motif in Cusa’s thought, its presuppositions and the original way he returns to it while thinking about the art of nature and the nature of art. We conclude that the relationship between art and nature is based on an aesthetic ontology, an aesthetic cosmology and an aesthetic anthropology, in which the true beauty develops in nature successive images of itself.